An American Investor in the Theatre Industry of Budapest: Ben Blumenthal (1883–1967): A Personal and Professional Biography - Heltai, Gyöngyi (Historical Studies on Central Europe, 2022)
In the interwar period, an American theatre and film entrepreneur had a determinant impact on the private theatre sector of Budapest. Ben Blumenthal (1883–1967) ran the Vígszínház (Comedy Theatre) in 1920–1926 and owned its building in 1920–1949. In addition, Blumenthal financed the operation of the Fővárosi Operettszínház (Budapest Operetta Theatre) in 1922–1926. Although from a global perspective, Blumenthal does not belong to the group of legendary US theatre or movie producers, in the context of Hungarian theatre culture, he was the most influential mediator in Hungarian–American cultural relations. The study aims to piece together the undiscovered elements of Blumenthal’s personal and professional biography and to discuss how his activities were evaluated from the American and the Hungarian perspectives. Special emphasis will be given to the US and Hungarian entertainment press: Blumenthal’s interviews on his Hungarian theatres, articles on Blumenthal’s position in the transnational producers’ hierarchy, and representation of the Vígszínház in the US entertainment press. The aim is to assess the significance of Blumenthal’s Budapest business activities within his entire career.